2006
DOI: 10.1080/14034940510032374
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in relation to employment status during different levels of unemployment

Abstract: The level of unemployment seems to have no major influence on the mortality risk. Future interventions for the non-employed groups should focus on preventing avoidable mortality, such as injury and suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…These results were in line with previous research. 2,4 However, work-related factors-physical and psychological demands and demands for learning at work-were not related to mortality in contrast to certain work strain models 9 and some earlier studies focusing on cardiovascular mortality among industrial employees. 17 These different findings may be due to the fact that we were not able to focus on cardiovascular mortality, which especially has been shown to be linked to stress and strain at work, because of the low number of cases in each of the diagnosis category per comparison group.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…These results were in line with previous research. 2,4 However, work-related factors-physical and psychological demands and demands for learning at work-were not related to mortality in contrast to certain work strain models 9 and some earlier studies focusing on cardiovascular mortality among industrial employees. 17 These different findings may be due to the fact that we were not able to focus on cardiovascular mortality, which especially has been shown to be linked to stress and strain at work, because of the low number of cases in each of the diagnosis category per comparison group.…”
Section: Discussionmentioning
confidence: 86%
“…[1][2][3][4] However, no agreement exists as to whether the health and well-being of the employed population are unevenly distributed between permanent and temporary employees. Temporary employment can be defined as paid employment relations other than those with unlimited duration, including fixed-term contracts as well as work done on call and through temporary-help agencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Swedish studies on somatic and psychological symptoms (Novo, Hammarströ m and Janlert, 2000) and mortality risk (Å hs and Westerling, 2006) among the unemployed did not find any noticeable variation with overall unemployment level. A Greek study even found worse health effects of being unemployed when unemployment is common (Drydakis, 2015), and a Canadian study could not confirm that effects of unemployment on health vary with unemployment rates (Beland, Birch and Stoddart, 2002).…”
Section: Previous Researchmentioning
confidence: 99%
“…I OECDstudien er resultater for enkeltland ikke oppgitt, men de nordiske landene er med i gruppen av land med høyest offentlige utgifter til sosiale formål, hvor sammenhengen er svakere enn for OECD-landene som helhet. Lignende studier er så vidt vites ikke foretatt i Norge, mens resultater fra Sverige og Finland er motstridende (62)(63)(64)(65)(66)(67). Studier fra USA tyder på at konjunkturene også er positivt forbundet med forekomsten av akutte og (i noe mindre grad) kroniske helseproblemer (68), samt med helsemessige risikofaktorer som røyking, høyt alkoholforbruk, lav fysisk aktivitet, overvekt og fedme, undervekt og usunt kosthold (52,69,70).…”
Section: Konjunkturer Og Sykdom/dødelighetunclassified